Regaining water swallowing function in the rehabilitation of critically ill patients with intensive-care-unit acquired muscle weakness. Issue 13 (19th June 2018) - Thomas, Simone; Sauter, Wolfgang; Starrost, Ulrike; Pohl, Marcus; Mehrholz, Jan
Abstract: Purpose: Treatment in intensive care units (ICUs) often results in swallowing dysfunction. Recent longitudinal studies have described the recovery of critically ill people, but we are not aware of studies of the recovery of swallowing function in patients with ICU-acquired muscle weakness. This paper aims to describe the time course of regaining water swallowing function in patients with ICU-acquired weakness in the post-acute phase and to describe the risks of regaining water swallowing function and the risk factors involved. Methods: This cohort study included patients with ICU-acquired muscle weakness in our post-acute department, who were unable to swallow. We monitored the process of regaining water swallowing function using the 3-ounce water swallowing test. Results: We included 108 patients with ICU-acquired muscle weakness. Water swallowing function was regained after a median of 12 days (interquartile range =17) from inclusion in the study and after a median of 59 days (interquartile range= 36) from the onset of the primary illness. Our multivariate Cox Proportional Hazard model yielded two main risk factors for regaining water swallowing function: the number of medical tubes such as catheters at admission to the post-acute department (adjusted hazard ratio [HR] = 1.282; 95% confidence interval [CI]: 1.099–1.495) and the time until weaning from the respirator in days (adjusted HR =1.02 per day; 95%CI: 0.998 to 1.008). Conclusion: We describe a time course for regaining water swallowing function based on daily tests in the post-acute phase of critically ill patients. Risk factors associated with regaining water swallowing function in rehabilitation are the number of medical tubes and the duration of weaning from the respirator. Implications for rehabilitation: Little guidance is available for the management of swallowing dysfunction in the rehabilitation of critically ill patients with intensive-care-units acquired muscle weakness. There is a time dependent pattern of recovery from swallowing dysfunction with daily water swallowing tests in the post-acute phase of critically ill patients. Daily water swallowing tests can be used to test swallowing dysfunction in the post-acute phase of critically ill patients The amount of medical tubes and the duration of weaning from respirator are associated risk factors for recovery of swallowing dysfunction.